2016
DOI: 10.1186/s40535-016-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel fuzzy document-based information retrieval scheme (FDIRS)

Abstract: BackgroundPrediction or forecasting is both an art as well as science. The process and outcome of forecasting have long been a matter of research and still are in its childhood state. We can devise numerous ways of modeling a phenomenon and predict its outcome, but there are no universal methods using which we can model every phenomena. Modeling of linear systems is comparatively simpler than dynamical systems. Stock markets are completely chaotic and dynamic systems which are both time and sentiment driven. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Relevance feedback is the main data source for constructing these user profiles. Relevance feedback has been investigated by several researchers [69] [9] [61] [53]. Previous research has analysed user behaviour and found a significant relationship between the time spent on reading Usenet news and the interest level of the user.…”
Section: A Relevance Feedbackmentioning
confidence: 99%
“…Relevance feedback is the main data source for constructing these user profiles. Relevance feedback has been investigated by several researchers [69] [9] [61] [53]. Previous research has analysed user behaviour and found a significant relationship between the time spent on reading Usenet news and the interest level of the user.…”
Section: A Relevance Feedbackmentioning
confidence: 99%
“…[4][5][6][7], it is usually considered that the view that provides more information is known as the "Japanese candlesticks chart" [8][9][10]. The trading techniques based on Japanese candlesticks are based on thorough research conducted at the Rice Market in Osaka by the trader Munehisa Homma during the eighteenth century, who recorded his rules in 1755 in the book entitled "The Fountain of Gold-The Three Monkey Record of Money" [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%